Enhanced Antimicrobial and Antibiofilm Effect of New Colistin-Loaded Human Albumin Nanoparticles - Sara Scutera; Monica Argenziano; Rosaria Sparti; Federica Bessone; Gabriele Bianco; Chiara Bastiancich; Carlotta Castagnoli; Maurizio Stella; Tiziana Musso; Roberta Cavalli (MDPI AG, 2021)
Multidrug-resistant (MDR) Gram-negative bacteria (GNB), such as Acinetobacter and Klebsiella, are responsible for severe hospital-acquired infections. Colistin, despite its toxicity and low tissue penetration, is considered the last resort antibiotic against these microorganisms. Of concern, the use of Colistin has recently been compromised by the emergence of Colistin resistance. Herein, we developed a new formulation consisting of multifunctional chitosan-coated human albumin nanoparticles for the delivery of Colistin (Col/haNPs). Col/haNPs were in vitro characterized for encapsulation efficiency, drug release, stability and cytotoxicity and were evaluated for antibacterial activity against MDR GNB (Acinetobacter baumannii and Klebsiella pneumoniae). Col/haNPs showed sizes lower than 200 nm, high encapsulation efficiency (98.65%) and prolonged in vitro release of Colistin. The safety of the nanoformulation was demonstrated by a negligible cytotoxicity on human fibroblasts and hemolytic activity. Col/haNPs evidenced a high antibacterial effect with a significant decrease in MIC values compared to free Colistin, in particular against Col-resistant strains with a pronounced decline of bacterial growth over time. Moreover, Col/haNPs exhibited an inhibitory effect on biofilm formation that was 4 and 60 fold higher compared to free Colistin, respectively for Colistin susceptible and resistant A. baumannii. Our findings suggest that Col/haNPs could represent a promising Colistin nanocarrier with high antimicrobial activity on MDR GNB.